Zoo animal and wildlife immobilization and anesthesia - West, Gary (Gary Don), 1969-; Heard, Darryl J.; Caulkett, Nigel (Ames, Iowa : John Wiley & Sons Inc., 2014)
Zoo Animal and Wildlife Immobilization and Anesthesia, Second Edition is a fully updated and revised version of the first comprehensive reference on anesthetic techniques in captive and free-ranging wildlife. Now including expanded coverage of avian and aquatic species, this exhaustive resource presents information on the full range of zoo and wildlife species. Covering topics ranging from monitoring and field anesthesia to CPR and euthanasia, the heart of the book is devoted to 53 species-specific chapters providing a wealth of information on little-known and common zoo and wildlife a.
Airway Idiopathic TraumaCleaning and Disinfection; References; 4: Thermoregulation; Monitoring Body Temperature; Hypothermia; Perioperative Heat Loss; Consequences of Hypothermia; Perioperative Hypothermia: Prevention and Treatment; Hyperthermia; References; 5: Oxygen Therapy; Why O2?; Hypoxemia and Hypoxia; What Causes Hypoxemia?; What Causes Hypoxia?; Oxygen Sources; High Pressure Oxygen Cylinders; Portable Oxygen Concentrators; Liquid Oxygen Containers; Methods of Administering Oxygen; Intranasal Oxygen; Flow-by Oxygen; Intra/Transtracheal Oxygen; Humidification or Not?
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Anesthesia -- veterinary; Animals, Wild; Animals, Zoo; Immobilization -- veterinary; Veterinary anesthesia; Animal immobilization; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Animal immobilization; Veterinary anesthesia; Animal immobilization; Immobilization -- Veterinary; Veterinary anesthesia; Electronic books; Electronic books